Debate in the USA Swaggart vs Deedat - Deedat, Ahmed (Kuala Lumpur : Saba Islamic Media)
The famous debate between Sh. Ahmed Deedat and Rev. Jimmy Swaggart in the United states of America on the topic' Is The Bible True Word of god?'
Keywords: Qur'an -- Relation to the Bible; Bible -- Comparative studies; Religions